Unlocking archival maps of the Hornsund fjord area for monitoring glaciers of the Sørkapp Land peninsula, Svalbard - J. Dudek; M. Pętlicki; M. Pętlicki (Earth System Science Data, 2023)
Archival maps are an important source of information on the state of glaciers in polar zones and are very often basic research data for analysing changes in glacier mass, extent, and geometry. However, basing a quantitative analysis on archival maps requires that they be standardised and precisely matched against modern-day cartographic materials. This can be achieved effectively using techniques and tools from the field of geographic information systems (i.e. GIS). The objective of this research was to accurately register archival topographic maps of the area surrounding the Hornsund fjord (southern Spitsbergen) published by the Polish Academy of Sciences and to evaluate their potential for use in studying changes in the geometry of glaciers in the north-western part of the Sørkapp Land peninsula in the following periods: 1961–1990, 1990–2010, and 1961–2010. The area occupied by the investigated glaciers in the north-western Sørkapp Land decreased in the years 1961–2010 by 45.6 km2, i.e. by slightly over 16 %. The rate of glacier area change varied over time and amounted to 0.85 km2 yr−1 in the period 1961–1990 and sped up to 1.05 km2 yr−1 after 1990. This process was accompanied by glacier surface lowering by about 90–100 m for the largest land-terminating glaciers on the peninsula and by up to more than 120 m for tidewater glaciers (above the line marking their 1984 extents). The dataset is now available from the Zenodo web portal: https://doi.org/10.5281/zenodo.4573129 (Dudek and Pętlicki, 2021).